2021
DOI: 10.3389/fpsyg.2021.630268
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of Factors Contributing to the Acceptance of Online Health Misinformation

Abstract: This study examined factors including health-related anxiety, preexisting misinformation beliefs, and repeated exposure contributing to individuals’ acceptance of health misinformation. Through a large-scale online survey, this study found that health-related anxiety was positively associated with health misinformation acceptance. Preexisting misinformation beliefs, as well as repeated exposure to health misinformation, were both positively associated with health misinformation acceptance. The results also sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
38
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(66 citation statements)
references
References 52 publications
5
38
1
Order By: Relevance
“…For example, people of color accepted more misinformation than white people. [4,42] offered an examination of factors contributing to the acceptance of online health misinformation). Lower socioeconomic status, older age, and lower educational level groups are also disproportionally impacted by misinformation [48].…”
Section: Results Of Misinformation and Online Educationmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, people of color accepted more misinformation than white people. [4,42] offered an examination of factors contributing to the acceptance of online health misinformation). Lower socioeconomic status, older age, and lower educational level groups are also disproportionally impacted by misinformation [48].…”
Section: Results Of Misinformation and Online Educationmentioning
confidence: 99%
“…It is worthy to mention that among the results found by this line of research, studies also have shown contradictory results. For example, some study argued that males tend to trust misinformation more than females [48], while other study contended that females accepted more health misinformation than their male counterparts [42].…”
Section: Results Of Misinformation and Online Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…Social media is regarded as a powerful global medium that influences people's perceptions of the world and their role in it [31]. Social media has raised critical concerns as context due to its popularity [3] as well as the rapid spread of fake news, thus causing potentially detrimental effects both on individuals and society [17,32]. In particular, the rapid spread of false information on Twitter has caused concern [3,17,18].…”
Section: Overview Of Key Conceptsmentioning
confidence: 99%
“…The field of misinformation is growing. Misinformation research has been growing rapidly on topics such as COVID 19 [2,4,48], vaccine [6; 9, 30, 49], climate change [13,16,36], medical concerns [56], communication [8], memory [22], cognitive impacts on reading [45], new literacies [11], online education [9], political studies [11,1], and diversity [42] etc.…”
Section: Review Of Related Literaturementioning
confidence: 99%